Fire Risk in Traditional Villages of Sumba, Indonesia - Setya Tantra; Peter Brimblecombe (Heritage, 2022)
Fire is a global problem for traditional villages, especially those dominated by the use of wood and thatch. These places are often crowded, which leads to the rapid spread of fire. The traditional villages on the island of Sumba are architecturally striking, with their tall houses interspersed with ancestral tombs. They are set on an island of grassland landscapes managed using fire. There is little local ability to suppress village fires as they are remote from firefighting services and access to the dwellings is poor. Documentary evidence along with satellite imagery of hotspots have been used to trace the fires on Sumba since 2001. Little meteorological data are accessible for Sumba, so we have used global homogenized records, reassessments and projections of climate to examine long-term change in Sumba. There is a dry season in July–September, which corresponds with the period of most frequent fires. The number of dry-season fires correlates with the number of consecutive dry days, which has been used to establish a likely increase in the potential for fires in the future. There is increased effort to reduce the impact of village fires. Approaches could include reducing the flammability of traditional materials, detection systems and enhanced support of village firefighting capabilities. These may be difficult to introduce given the importance of the architectural heritage and the religious context of village layout, design and governance.